Perancangan Workbench Universal Dengan Mekanisme Scissor Lift Manual - Gurruh Dwi Septano; Sayid Bahri Sriwijaya; Ikbal Ikbal; Linggar Ajong; Alfan Taftazani (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2023)
The study purpose was to design and preliminarily validate a universal adjustable workbench that supports seated and standing bench-work activities in educational workshops, overcoming ergonomic limitations of fixed-height benches.Materials and methods. An engineering design–fabrication–testing approach was applied. The prototype was modeled in Autodesk Inventor and built using a manual scissor-lift mechanism actuated by an M10 grade 4.6 threaded bar. The work surface measured 1200 × 700 mm with an adjustable height range of 75–110 cm. The frame used hollow steel sections (40×40×2.3 mm and 30×30×2 mm; mild steel, σy ≈ 240 MPa) and a double-layer 10 mm plywood tabletop. Actuator capacity was analytically verified using an effective stress area of 58 mm², yield strength 240 MPa, and a safety factor (SF) of 2. Performance evaluation included incremental static loading (100–280 kg), repeated height adjustment (≥50 cycles), and eccentric-load stability testing.Results. The threaded-bar analysis estimated a yield-limit capacity of 6,276 N (≈640 kg), corresponding to a recommended safe working load of 320 kg (SF=2). Physical tests up to 280 kg showed stable lifting and height holding with no permanent deformation of the screw or frame; cycle and eccentric-load tests indicated reliable operation under repeated and uneven loading within the tested range.Conclusions. The manual scissor-lift adjustable workbench achieved functional adjustability and demonstrated promising structural stability for workshop/laboratory use. Further work should extend load testing to the recommended safe limit and add quantitative ergonomic posture assessment to substantiate ergonomic benefits.